Mastering pharmacy licensure and certification : a case-based review - Kosegarten, David C.; Pisano, Douglas J.; Vogenberg, F. Randy (Boston : The McGraw-Hill, Inc., 2000)
As the practice and profession of pharmacy has changed, so has the need to demonstrate minimum competencies as a pharmacist.
Coronary artery disease -- Hypertension -- Seizure disorders -- Buffer solutions -- Bacteremia and sepsis -- Human immunodeficiency virus and acquired immuno deficiency syndrome (HIV/AIDS) -- Oncology/Breast cancer -- Medicinal chemistry case #1 -- Panic disorder -- Renal transplantation -- Controlled substances act (C.S.A) -- Arrhythmias -- Hypertension -- Seizure disorders -- Antibiotic suspensions
Includes index.
Keywords: PHARMACY -- CASE STUDIES; PHARMACY -- EXAMINATIONS -- STUDY GUIDES